2017
DOI: 10.3949/ccjm.84a.15051
|View full text |Cite
|
Sign up to set email alerts
|

ADHD: Overdiagnosed and overtreated, or misdiagnosed and mistreated?

Abstract: In today's changing medical climate, physicians need to treat attention-deficit/hyperactivity disorder (ADHD) better and more cost-effectively. The authors review recommendations supported by recent research and offer simple practices that integrate medicine and behavioral health for patients with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
(61 reference statements)
3
13
0
5
Order By: Relevance
“…We found that only patients who felt their economic status were higher than the average was less likely to be misdiagnosed. This is in line with the findings from previous studies which state that people with low income are more likely to lead to misdiagnosis [ 15 , 16 ]. However, limited findings were reported when patients living with RDs, as seen from our data, RDs do not ‘discriminate’ in terms of gender, age, ethnicity, residential area, or educational levels.…”
Section: Discussionsupporting
confidence: 93%
“…We found that only patients who felt their economic status were higher than the average was less likely to be misdiagnosed. This is in line with the findings from previous studies which state that people with low income are more likely to lead to misdiagnosis [ 15 , 16 ]. However, limited findings were reported when patients living with RDs, as seen from our data, RDs do not ‘discriminate’ in terms of gender, age, ethnicity, residential area, or educational levels.…”
Section: Discussionsupporting
confidence: 93%
“…We found that only patients who felt their economic status were higher than the average was less likely to be misdiagnosed. This is in line with the ndings from previous studies which state that people with low income are more likely to lead to misdiagnosis [15,16]. However, limited ndings were reported when patients living with RDs, as seen from our data, RDs do not 'discriminate' in terms of gender, age, ethnicity, residential area, or educational levels.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that physician contact and engagement/partnership with families play a major role in both medication adherence and improved ADHD medication titration. 7,22 This supports the idea that more physician attention is needed in these populations.…”
Section: Discussionsupporting
confidence: 65%
“…The prescribe-and-wait method is the most common. 7 During this titration process, patient treatment adherence and physician contact play a key role in successful stimulant treatment. However, there is minimal research on the duration of titration.…”
Section: Introductionmentioning
confidence: 99%